2019
DOI: 10.1001/jamaneurol.2018.2808
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping the Supratentorial Cerebral Arterial Territories Using 1160 Large Artery Infarcts

Abstract: IMPORTANCE Cerebral vascular territories are of key clinical importance in patients with stroke, but available maps are highly variable and based on prior studies with small sample sizes. OBJECTIVE To update and improve the state of knowledge on the supratentorial vascular supply to the brain by using the natural experiment of large artery infarcts and to map out the variable anatomy of the anterior, middle, and posterior cerebral artery (ACA, MCA, and PCA) territories. DESIGN, SETTING, AND PARTICIPANTS In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 19 publications
1
76
0
Order By: Relevance
“…The collaterals described on computed tomography angiography after LVO are likely to be due to the work of the LA in conjunction with CoW (15,16). The contribution of this secondary collateral system has been observed in maps of infarct territory as relative sparing of the posterior and superior parts of the MCA territory (17,18) and in our earlier work on the computer model of the cerebral circulation (9).…”
Section: Introductionmentioning
confidence: 87%
“…The collaterals described on computed tomography angiography after LVO are likely to be due to the work of the LA in conjunction with CoW (15,16). The contribution of this secondary collateral system has been observed in maps of infarct territory as relative sparing of the posterior and superior parts of the MCA territory (17,18) and in our earlier work on the computer model of the cerebral circulation (9).…”
Section: Introductionmentioning
confidence: 87%
“…The inter-arterial watershed zone of the brain, also known as the inter-territorial border zone [21], is the portion of the brain that lies at the periphery of the supply of the main vessels of the brain, i.e. between the supply of the anterior cerebral artery (ACA), the posterior cerebral artery (PCA) and the middle cerebral artery (MCA).…”
Section: Introduction and Aimmentioning
confidence: 99%
“…1). In contrast, the watershed zone for adults has been outlined by mapping arterial infarctions from many patients [21].…”
Section: Introduction and Aimmentioning
confidence: 99%
“…These regions sustain many essential brain functions which contribute to critical symptomatology of acute stroke patients. They appear to be more frequently injured in the literature 4,8,9,13,[19][20][21][22][23][24] than any other brain areas. Several studies have connected the insula to stroke severity.…”
Section: Discussionmentioning
confidence: 99%
“…Probabilistic estimates of S, D and IBZ regions are of particular interest when considering the substantial spatial variability of the different vascular fields 24,37 . Lang et al 19 used the spatial distributions reported by van der Zwan et al 37 to study its impact on the topographical infarct characterization.…”
Section: Discussionmentioning
confidence: 99%